2009
DOI: 10.1007/s00234-009-0501-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obstetric complication severity on brain morphology in schizophrenia: an MR study

Abstract: Although confirmatory studies are needed, our findings would support the idea that environmental factors, in this case severe OCs, might partly contribute to ventricular abnormalities in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In accordance with our findings, Bersani and colleagues reported no effect of OCs on the bicaudate ratio (an indirect measure of caudate/ventricle size) in (n=47) male schizophrenia patients (Bersani et al, 2009).…”
Section: Effects Of Ocs On Brain Morphologysupporting
confidence: 93%
“…In accordance with our findings, Bersani and colleagues reported no effect of OCs on the bicaudate ratio (an indirect measure of caudate/ventricle size) in (n=47) male schizophrenia patients (Bersani et al, 2009).…”
Section: Effects Of Ocs On Brain Morphologysupporting
confidence: 93%
“…Etiological associations with prenatal exposure to infection, 8 9 obstetric complications, 10 and genetic vulnerabilities 11 12 support the notion that schizophrenia has a neurodegenerative etiology. In addition, cortical gray matter loss has been shown to be associated with childhood-onset schizophrenia.…”
Section: Introductionmentioning
confidence: 75%
“…Sixteen general symptom studies explored various aspects of medial temporal morphometry. Ten did not report any significant relationships between the presence or severity of TD and measures of medial temporal structure (Arango et al, 2003;Barta et al, 1990;Bersani et al, 2009;Guo et al, 2014;Kawasaki et al, 1997;Price et al, 2010;Sanfilipo et al, 2000;Szendi et al, 2006;Takahashi et al, 2006b;Yamasue et al, 2004). The pattern of findings amongst four of the remaining six studies indicated altered morphometry within the amygdala and hippocampus, particularly reductions in volume on the left side with greater positive or total TD (Bogerts et al, 1993;Fukuzako et al, 1996;Rajarethinam et al, 2001;Sallet et al, 2003b).…”
Section: Medial Temporal Lobe and Associated Subcortical Regionsmentioning
confidence: 97%